2017
DOI: 10.1097/md.0000000000006472
|View full text |Cite
|
Sign up to set email alerts
|

High expression of CD8 predicts favorable prognosis in patients with lung adenocarcinoma

Abstract: Lung carcinoma is the most common cause of malignant death worldwide. CD8+ T cells, as critical elements in antitumor immunity, could function as good prognostic indicators in various kinds of cancers such as renal cell carcinoma and colorectal cancer, but its prognostic role in lung adenocarcinoma is still unclear. The objective of this study was to explore the prognostic role of CD8 expression in lung adenocarcinoma.Paired tumor and adjacent noncancerous tissues were obtained from 102 patients with lung aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
1
22
0
1
Order By: Relevance
“…Twenty-three studies underwent pooled analysis ( Supplementary Table 1 , Supplementary Figure 1H ) [ 23 , 24 , 29 , 31 , 32 , 60 64 , 66 78 ]. Although CD8+ T cells in the general compartment was not associated with OS (HR 0.80; 0.56–1.15) or DFS (HR 0.70; 0.48–1.02), when analysed according to tumor or stroma compartment, the prognostic value of CD8+ T cells could be appreciated (Table 1 , Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-three studies underwent pooled analysis ( Supplementary Table 1 , Supplementary Figure 1H ) [ 23 , 24 , 29 , 31 , 32 , 60 64 , 66 78 ]. Although CD8+ T cells in the general compartment was not associated with OS (HR 0.80; 0.56–1.15) or DFS (HR 0.70; 0.48–1.02), when analysed according to tumor or stroma compartment, the prognostic value of CD8+ T cells could be appreciated (Table 1 , Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an increasing number of researchers [21][22][23][24][25][26][27][28][29] have paid great attention to the CD8 (+) TILs in the tumour microenvironment due to their anti-tumour effect. Gabrielson's research 21 illustrated that high numbers of CD8 (+) TILs significantly correlated with a low rate of recurrence and prolonged relapse-free survival in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Goode 22 showed that in high-grade serous ovarian cancer, high numbers of CD8 (+) TILs were significantly associated with improved OS. Ye 28 found that high numbers of CD8 (+) TILs predicted favourable prognosis in lung adenocarcinoma patients. These studies may indicate that CD8 (+) TILs are a prognostic biomarker that correlates with a favourable prognosis in solid tumours.…”
Section: Discussionmentioning
confidence: 99%
“…According to IHC staining, the expression of AKIP1 in the tumor and paired adjacent tissues was assessed by a semiquantitative scoring method based on the average intensity and percentage of positively stained tumor cells. 12 The score of intensity was assessed as follows: 0 (no staining), 1 (weak staining), 2 (moderate staining), and 3 (strong staining). The percentage of positively stained tumor cells was scored according to the following standard: 0, 0%; 1, <25%; 2, 26 ~ 50%; 3, 51 ~ 75%; and 4, >75%.…”
Section: Ihc and Assessment Of Akip1 Expressionmentioning
confidence: 99%